Wiedemann–Steiner Syndrome: A Rare Differential Diagnosis of Neurodevelopmental Delay and Dysmorphic Features - Carman, Kursat Bora; Kaplan, Emre; Aslan, Cefa Nil; Kocagil, Sinem; Cilinigr, Oguz; Yarar, Coskun (Journal of Pediatric Genetics, 2020)
Wiedemann–Steiner syndrome (WSS) is a rare genetic disorder characterized by dysmorphic features, neurodevelopmental delay, growth retardation, and hypertrichosis cubiti. It is caused by pathogenic variants in the KMT2A gene. Here, we report a child with WSS presented with neurodevelopmental delay. Genetic analysis revealed a heterozygous c.2312dupC (p.Ser774Valfs*11) variant at the KMT2A gene that was classified as pathogenic in dbSNP (rs1057518649). To the best of our knowledge, this is the first patient of WSS from Turkey. This case draws attention to the diagnosis of WSS in children with neurodevelopmental delay.
Keywords: Wiedemann–Steiner syndrome; genetic; children; neurodevelopmental delay; dysmorphic